Batrachochytrium dendrobatidis and Hannemania mite’s relationships with Mexican amphibians in disturbed environments - Jacinto-Maldonado, Mónica; Lesbarrères, David; Rebollar, Eria A.; Basanta, M. Delia; González-Grijalva, Belem; Robles-Morúa, Agustín; Álvarez-Bajo, Osiris; Vizuete-Jaramillo, Efraín; Paredes-León, Ricardo; Meza-Figueroa, Diana (Frontiers in Amphibian and Reptile Science, 2024)
The rapid transformation and pollution of ecosystems have severely impacted biodiversity. Specifically, anthropogenic activities have imposed adverse effects on amphibians, with evidence suggesting that these activities alter parasite and pathogen interactions within their hosts. To investigate these interactions in areas affected by different anthropogenic activities, our study focused on analyzing a pathogen and a parasite known to interact within the amphibian skin (spongy epidermis layer) and both compromising amphibian health: Batrachochytrium dendrobatidis (Bd), a fungus responsible for chytridiomycosis, a disease associated with massive population declines in amphibians and the Hannemania sp. mite in Mexico. Four sampling areas along the Sonora River were selected, representing different human activities: mining, livestock, wastewater discharge, agriculture, and one in an urban zone. We analyzed 135 amphibians across 10 anuran species. Among these, the most abundant species (Lithobates yavapaiensis) exhibited the highest prevalence of both pathogen and parasite (90.1% and 27.3%, respectively) and was significantly associated with the intensity of Bd-infection. The prevalence of Hannemania mites varied significantly across sampling sites as did Bd prevalence and infection load, with the highest Bd load found at the wastewater discharge site. A significant association between the intensity of Bd-infection and both mite abundance and amphibian species was observed when the sampling site was considered. Additionally, sites with Bd-positive individuals and Hannemania parasitism coincide with refractory elements characterized by mechanical or corrosion resistance. The persistence of these elements in the environment, along with the small particle size (<850 nm) found in sediments, poses a potential risk of internalization, bioaccumulation (e.g., Fe, Co, and Ti), and their transfer through the food chain. It is thus essential to consider monitoring environmental and biotic factors that modulate the relationships between parasites, pathogens, and amphibians if we are to propose conservation strategies adapted to disturbed environments.